Aveia branca e/ou casca de soja na dieta de bovinos alimentados com ou sem volumoso - Weise, Matheus Smidt (2016)
The aim of this work was to study the use of whole dry white oat grain (Avena sativa), soybean hulls (Glycine max L.), and the mixture of these ingredients (1:1), provided in two ways: with or without a roughage source on the diet. Sixty- eight male castrated steers, Charolais x Nelore crossbred, with initial average age of 20 months were used, distributed in a factorial scheme 3 x 2, with three energetic sources on the concentrate (white oat grain; soybean hulls and the mixture of these ingredients) and two ways of provision (with or without roughage). The roughage used was sorghum silage (Sorghum bicolor (L.) Moench), with roughage: concentrate of 50:50, based on DM. The ingestive behavior characteristics and the animal's performance response were measured and compared. The final weights of the steers did not differ statistically. The daily average gain of the mixture source (1.167 kg) was superior (P<0.05) to the soybean hulls (0.940 kg), being the oat grain intermediate (1.061 kg). It was observed higher (P<0.05) intake of dry matter and neutral and acid detergent fiber on the diets that contained roughage. Animals fed without roughage presented in the average better (P<0.05) feed conversion (6.291 kg) in relation to the animals fed with roughage (8.578 kg). Independently of the energetic source tested, steers fed with roughage remained more time (P<0.05) eating (4.23 h) and ruminating (7.88 h), compared to the ones fed without roughage (2.68 and 3.52 h, respectively). Steers fed with the energetic sources of oat grain and mixture, were more efficient in the dry matter intake (DM) when fed without roughage. On the average, steers fed without roughage were more efficient in the intake of neutral detergent fiber (NDF) and more efficient in the rumination of NDF. Steers fed with or without roughage presented difference (P<0.05) for the total chewing time (13.13 and 6.19h), for the number of ruminal bolus per day (502 and 184), and for the number of rumination chews (30,774 and 11,637, respectively). Steers from the soybean hulls energetic source chewed a few (P<0.05) number of times per ruminal bolus when fed without roughage (41.63), compared to the ones fed with roughage (62.66).